Nalar Islam Antroposentris (Mentransformasi Relasi Humanis Antarumat Beragama di Indonesia) - Wijaya, Aksin; Anggraini, Yulia (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Understanding of religion is influenced by the paradigm used by each person. So far, there are three paradigms that have developed among Indonesian Muslim intellectuals in particular, namely the theocentric Islamic paradigm, the theoanthropocentric Islamic paradigm and the anthropocentric Islamic paradigm. Each paradigm is based on a different method of reasoning with reference to the fundamental question, whether religion is a divine taklif or a human right. With the aim of critically analyzing the three paradigms and offering a new paradigm in understanding religion, this paper utilizes Abdul Karim Soros's taklif and human rights theory and the maqasyidi interpretation theory to analyze the verses of the Qur'an. The method of critical appreciation thinking is used to compile the framework of this paper. The results of the study show that Islam through its holy book is a holy book that is oriented towards the interests and welfare of humans, both in the world and in the hereafter. However, this welfare must remain bound by the holy book, although it does not mean completely rejecting the welfare that is born from humans as long as it does not conflict with the maqasyid of the holy book.